Understanding academic attitudes towards the ethical challenges posed by social media research - Carter, Christopher J.; Koene, Ansgar; Perez, Elvira; Statache, Ramona; Adolphs, Svenja; O'Malley, Claire; Rodden, Tom; McAuley, Derek (Association for Computing Machinery (ACM), 2016)
In this paper, we outline an online survey-based study seeking to understand academic attitudes towards social media research ethics (SMRE). As the exploratory phase of a wider research project, findings are discussed in relation to the responses of 30 participants, spanning multiple faculties and locations at one international university. The paper presents an empirical measure of attitudes towards social media research ethics, reflecting core issues outlined throughout the nascent Internet-mediated research (IMR) literature, in addition to survey questions relating to familiarity with SMRE guidance, and experience of reviewing SMRE proposals from students and/or as part of the university's research ethics committees (RECs). Findings indicate notable variance in academic attitudes towards the ethical challenges of social media research, reflecting the complexity of decision-making within this context and further emphasising the need to understand influencing factors. Future directions are discussed in relation to the tentative findings presented by the current study.